The Marketing Implications of Traditional and ICT-mediated Leisure Activities - Zorn, Steffen; Lee, R.; Murphy, J. (Taylor & Francis Ltd., 2012)
This study investigates the role of traditional and information and communication technology (ICT)-mediated leisure activities in consumer beahaviour. An online survey of 558 members and 1319 ex-members of an Australian DVD rental company gathered preferences for nine traditional leisure activities and seven ICT-mediated leisure activities. The results of a cluster analysis showed four clusters with significant cluster differences across leisure activities and across demographics and consumer behaviours. For practitioners, the study illustrates how profiling customers on their leisure preferences can increase advertising effectiveness, reflect loyalty and help predict customer lifetime value. For academia, the results reveal how another consumer dimension, leisure activities, relates to demographic and behavioural characteristics.